Functional and Antioxidant Potential of Beetroot, Mustard and Radish Microgreens Using Spectroscopic Techniques - Rizvi Anamta; Kumar Sailendra; Sharma Monica; Saxena Sangeeta (Agriculture)
Microgreens are tiny plants with a pair of cotyledon leaves, a short stem, and roots. These are considered as sustainable superfoods that are easy to grow and rich in bioactive compounds. Among functional foods, microgreens are particularly noteworthy because they have enticing health-promoting properties due to their rich biochemical profiles which contribute to antioxidant activities. In this study, three varieties of microgreens, Beta vulgaris, Raphanus sativus and Brassica juncea, were studied to estimate phytochemicals such as total chlorophyll, carotenoids, flavonoids, and phenols. Additionally, the antioxidant potentials of methanolic extracts of these microgreens were determined by various assays such as 2, 2-diphenyl, 1-picrylhydrazyl and H2O2 scavenging assay, total antioxidant capacity and reducing power assay. Moreover, Fourier transform infrared spectroscopic fingerprinting was conducted to determine the functional groups associated with bioactive phytochemicals present in all microgreens. Scanning Electron Microscopy and Energy Dispersive X-ray Spectroscopic studies were also conducted to explore the morphological and elemental profiling of each microgreen. The results revealed that the studied microgreens have rich phytochemical compositions and great antioxidant potential. Furthermore, the functional groups of bioactive compounds identified in each were extensively associated with antioxidant activities. Therefore, micro-greens can be recommended as promising superfoods that can be incorporated into the mainstream diet to improve human health.